Atorvastatin unveiling primary biliary cholangitis and autoimmune hepatitis overlap syndrome in an older adult: A case report - Khadijat-Ul-Kurba Hashim; Zuhra Hamzah; Ummul Afilah Omar; Nurwahyuna Rosli (Malaysian Family Physician)
Although statins are generally well-tolerated, recent reports have linked their use to autoimmune liver disease. We present the case of a 70-year-old woman who developed hepatocellular injury 4 months after switching from simvastatin to high-intensity atorvastatin. Discontinuation of atorvastatin led to a gradual improvement in liver function over 3 months; however, her rising LDL(low-density lipoprotein) levels prompted a rechallenge with simvastatin, resulting in recurrent liver function derangement. Despite cessation, the liver enzyme levels continued to rise. Positive autoantibodies, including antinuclear antibodies, anti-mitochondrial M2 and immunoglobulins (i.e. IgA and IgG), along with a liver biopsy, confirmed an overlapping syndrome of primary biliary cholangitis and autoimmune hepatitis. Treatment with prednisolone led to normalisation of liver function, and the patient remained stable on azathioprine and ursodeoxycholic acid. This case underscores the importance of vigilant liver function monitoring, caution when rechallenging statins and the potential for statin therapy to unmask underlying autoimmune liver disease.